New possibilities of thetherapy of patients with atopic dermatitis with Janus kinaseinhibitors - N. V. Zilberberg; M. M. Kokhan; Yu. V. Keniksfest (Лечащий Врач)
Atopic dermatitis is a common chronic dermatosis of multifactorial nature with prevalence of genetic component and complex pathogenesis. In the pathogenesis of atopic dermatitis, an important role is played by hereditary determinism, leading to a violation of the state of the skin barrier, defects of the immune system (stimulation of Th2 cells with subsequent overproduction of IgE); hypersensitivity to allergens and nonspecific irritants, colonization of the skin and mucous membranes by pathogenic microorganisms, as well as an imbalance of the autonomic nervous system with an increase in the production of inflammatory mediators. The genetic factors for the development of atopic dermatitis include the presence of a mutation in the filaggrin gene, leading to dysfunction of the epidermal barrier in atopic dermatitis, as well as a family history of atopic dermatitis and other atopic diseases. The development of an inflammatory reaction in the skin with the participation of T-lymphocytes is associated with defects in the immune system. In the acute phase of the disease, the Th2 response predominates, when Th2 cells are stimulated with subsequent overproduction of specific IgE; in chronic – there is a switch from Th2- to Th1-immune response. A number of interleukins and IFN-?, which require the participation of the JAK/STAT signaling system, including Janus kinase, are involved in the pathophysiological mechanisms of atopic dermatitis. The disease usually develops in the first 2 years of life, and in 2/3 of cases persists into adulthood, while 45% of all cases of onset of the disease occur in the first 6 months of life: in 60% of cases, the disease develops during the first year of life and in 85% cases under the age of 5 years. In adulthood, the skin process persists in 38-42% of patients. Over time, approaches to the treatment of thedermatosis have undergone significant changes. This article provides an up-to-date review of the results of clinical trials of the drug upadacitinib in the treatment of atopic dermatitis.